2019
DOI: 10.1016/j.jveb.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Crib biting and equine gastric ulceration syndrome: Do horses that display oral stereotypies have altered gastric anatomy and physiology?

Abstract: Equine Gastric Ulceration Syndrome (EGUS) and Crib biting are two separate conditions suffered by horses. Previous research has hypothesised causal relationships between these two conditions, whereby the behavior is driven by a requirement to stimulate saliva production to buffer gastric juice. However to date there is limited empirical evidence to support this notion. To identify if the anatomy and physiology of the equid stomach differed in crib biting (CB) horses and non-crib biting controls (N-CB) a two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…However, a direct connection between the behavioural disorder "crib-biting" in horses and the occurrence of stomach ulcers has not been proven. This indicates that both diseases result from housing and management related stress and are not interdependent [52,53]. Consequently, horses have evolved in a way that requires continuous food intake, from an ethological (natural behaviour) and a physiological (digestive system) point of view.…”
Section: Introductionmentioning
confidence: 99%
“…However, a direct connection between the behavioural disorder "crib-biting" in horses and the occurrence of stomach ulcers has not been proven. This indicates that both diseases result from housing and management related stress and are not interdependent [52,53]. Consequently, horses have evolved in a way that requires continuous food intake, from an ethological (natural behaviour) and a physiological (digestive system) point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Por meio da ação de músculos circulares, movimentos peristálticos formam anéis de constrição na parede esofágica, reduzem o lúmen e empurram o bolo alimentar aboralmente. Ao chegar à porção distal do esôfago, o esfíncter distal se abre e a ingesta entra no estômago (DANIELS et al, 2019).…”
Section: Anatomia E Fisiologia Do Trato Gastrointestinal (Tgi) Equinounclassified
“…O intestino delgado dos equinos possui comprimento médio de 20 metros, sendo dividido em: duodeno, jejuno e íleo (DANIELS et al, 2019). A mucosa possui vilosidades de 0,5 a 1 mm, revestidas por células epiteliais com microvilosidades destinadas a aumentar a superfície absortiva, células caliciformes secretoras de muco e glândulas secretoras de suco entérico (RIBEIRO et al, 2019).…”
Section: Anatomia E Fisiologia Do Trato Gastrointestinal (Tgi) Equinounclassified
See 1 more Smart Citation
“…Cribbing and other stereotypies are associated with ESGD and considered to be coping mechanisms, suggesting a link with stress [18,19]. Daniels et al found no difference in gastric anatomy and physiology between crib-biting and non-crib-biting horses and suggested that there is no direct link between crib-biting and EGUS, but that both may be related to physiological and environmental stress [20]. It has also been demonstrated that horses with EGUS experience more oxidative stress than healthy horses [21].…”
Section: Introductionmentioning
confidence: 99%